ZnCr2O4@ZnO/g‐C3N4: A Triple‐Junction Nanostructured Material for Effective Hydrogen and Oxygen Evolution under Visible Light. Issue 9 (6th June 2017) - Patnaik, Sulagna; Sahoo, Dipti P.; Mohapatra, Lagnamayee; Martha, Satyabadi; Parida, Kulamani
Abstract: A triple‐junction nanostructured material consisting of porous exfoliated graphitic carbon nitride (g‐C3 N4 ) nanosheets, ZnO, and ZnCr2 O4 is prepared by a one‐pot synthesis method through the calcination of a mixture of urea, thiourea, and Zn–Cr layered double hydroxide (LDH) at 450 °C. The structural, morphological, and optical properties of the prepared nanocomposites are characterized by various physicochemical techniques. This synthesis process simultaneously makes the material porous, produces exfoliated sheets of g‐C3 N4, and disperses mixed metal oxides on the surface of g‐C3 N4 owing to the slow evolution of significant amount of gases such as H2 O, CO2, NH3, and H2 S. The dispersion of ZnO and ZnCr2 O4 on the surface of the g‐C3 N4 exfoliated nanosheets results in a preferable resolution for visible‐light‐induced photocatalytic H2 and O2 evolution. An optimal g‐C3 N4 content (60 %) in the ZnCr2 O4 @ZnO/g‐C3 N4 nanostructured composite results in maximum H2 (847 μmol in 2 h) and O2 (455 μmol in 2 h) production in the presence of CH3 OH and AgNO3, respectively, as sacrificial reagents. The apparent conversion efficiencies for H2 and O2 evolution are 28.01 and 15.0 %, respectively. The increased photocatalytic activity is attributed to the proper alignment of the band structure, synergistic effects owing to the good coordination between g‐C3 N4 (Lewis base) and Zn II ions (Lewis acid), and the suppression of electron–hole recombination owing to the formation of g‐C3 N4 nanosheets. Abstract : The power of three : A triple‐junction nanostructured composite of ZnCr2 O4 @ZnO with graphitic carbon nitride (g‐C3 N4 ) is prepared by an in situ calcination method and shows enhanced H2 and O2 evolution under visible light.